Does Tax Avoidance Matter in Sustainaility Reporting-Financial Performance Relationship: Evidence From Indonesia - -, Supriyati - (AKRUAL: JURNAL AKUNTANSI)
Financial performance is a measure of the success of company operations. Optimum financial performance is said to be achieved when the company operating successfully increases company turnover. Sustainability reporting uncovers financial and non-financial aspects of this company operates. The objective of this research is to examine the effect of sustainability reporting on financial performance with tax avoidance as a mediating variable. This research was conducted in 58 companies that conducted sustainability reporting in the 2014-2018 period. Data were analyzed with regression and causal step testing. This research has some results, which among others are: that sustainability reporting has a positive effect on corporate financial performance, and that tax avoidance has a negative effect on corporate financial performance. It was also found that tax avoidance is not aÂ mediating variable for the effect of sustainability reporting on corporate financial performance